THE THEORETICAL FOUNDATIONS OF STATE LIABILITY IN PRIVATE INTERNATIONAL LAW - Kodirjonov Azizbek Murodjonovich (Scholar Express Journals, 2025)
State liability occupies a central position in the field of public international law, delineating the conditions under which a state may be held liable for breaches of its international obligations. However, when these breaches intersect with cross-border private disputes, a distinct layer of complexity emerges.
Keywords: public international law; obligations; breaches